A prosa literária de Bruno de Menezes em perspectiva dialógica - Aquino, Ana Cleide Guimbal de [UNESP] (2014)
Bruno de Menezes has a vast work, which goes through prose, poetry and folklore. His poetry is part of his most studied, so this research we chose to analyze two works in prose: Maria Dagmar (novel, 1924) and Candunga: cenas da migração nordestina na zona bragantina (novel, 1954). With theoretical foundation based on the works of Mikhail Bakhtin and his Circle, we examined the corpus in order to characterize this literature, the social values it conveys, the style, the discursive project of the author and architectural composition of the works. The research that now presents itself, emerged from some images, attributed by critics to the writer Bruno de Menezes, as the writer of the marginalized, the voice that comes out of the drums (Benedito Nunes), the operator of the verse (José Arthur Bogéa), the soul of the people (Abguar Bastos), the heart of the suburb, the yard and the town (Dalcídio Jurandir), the bohemian poet of Belém (Ramayana Chevalier), the proletarian poet/poet of simple people (Santana Marques), the voice of our people (Machado Coelho), Voodoo Priest of the poetry of the earth (Puget Gentil), authentic interpreter of people of color (Pedro Tupinambá), etc. All these names can be found sparsely in the magazine Asas da Palavra (1996), and in the essays in the book Bruno de Menezes ou a sutileza da transição (1994). As a result of the analysis, in Maria Dagmar, confirmed some of the epithets attributed by critics and present dialogical relations with other texts, one set by the author Bruno de Menezes, the novel as A Ruiva, the Fialho d'Almeida. In Candunga, we realize that the main concern of the work is between culture and identity, especially the Amazonian Caboclo and the Northeast, speaking in customs, tradition confirming in this way the image assigned to the author-creator as ―the voice of our people‖, ―disseminator of culture‖, and ―writer of... (Complete abstract eletronic access below)